PENGARUH BIAYA PRODUKSI, BIAYA OPERASIONAL DAN BIAYA PEMASARAN TERHADAP LABA PERUSAHAAN PADA PT NIPPON INDOSARI CORPINDO TBK PERIODE 2014-2023 Riska Putri Ningtias - Ningtias, Riska Putri; Reza Octovian (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this study is to determine the effect of Production Costs, Operational Costs and Marketing Costs on Net Profit at PT Nippon Indosari Corpindo Tbk for the 2014-2023 Period, both partially and simultaneously. The research method used is a quantitative method. The population used is the Financial Report of PT Nippon Indosari Corpindo Tbk for the 2014-2023 Period for 10 (ten). The sample used is the Profit and Loss Report of PT Nippon Indosari Corpindo Tbk for the 2014-2023 Period. Data analysis in this study uses classical assumption tests, multiple linear regression analysis, hypothesis testing and determination coefficient analysis. The results of this study are multiple linear regression equations of Y = (-15.189.932) + 0.616X1 – 0.404X2 + 0.326X3. Partially, the Production Cost variable has a positive and significant effect on Net Profit with the result of t count > t table or (6.676 > 2.447) with a significance level of 0.001 < 0.05. The Operational Cost variable also has a negative and significant effect on Net Profit with the result of t count > t table or (-2.805) > (-2.447) with a significance level of 0.031 < 0.05. While the Marketing Cost variable has no significant effect on Net Profit with the result of t count < t table or (0.501 < 2.447) with a significance level of 0.634 > 0.05 Simultaneously, Production Cost, Operational Cost and Marketing Cost have a significant effect on Net Profit with the value of F count > F table, namely (16.934 > 4.76) with a significance level of 0.002 < 0.05. The coefficient of determination is 89.4%, the remaining 0.106% is influenced by other variables and factors.